Exploring the gap between hand washing knowledge and practices in Bangladesh: a cross-sectional comparative study - Rabbi Sifat E; Dey Nepal C (BMC, 2013)
Abstract Background Hand washing is considered as one of the most effective hygiene promotion activities for public health in developing countries. This study compared hand washing knowledge and practices in BRAC's water; sanitation and hygiene (WASH) programme areas over time. Methods This study is a cross-sectional comparative study between baseline (2006), midline (2009) and end-line (2011) surveys in 50 sub-districts from the first phase of the programme. Thirty thousand households from 50 sub-districts were selected in two steps: i) 30 villages were selected from each sub-district by cluster sampling, and ii) 20 households were chosen systematically from each village. The matched households were considered (26,404 in each survey) for analysis. Data were collected from households through face-to-face interview using a pre-tested questionnaire. Respondents were the adult female members of the same households, who had knowledge of day-to-day household activities related to water, sanitation and hygiene. Results A gap between perception and practice of proper hand washing practices with soap was identified in the study areas. Hand washing practice with soap before eating was much lower than after defecation. In baseline data, 8% reported to wash their hands with soap which significantly increased to 22% in end line. Hand washing knowledge and practices before cooking food, before serving food and while handling babies is considerably limited than other critical times. A multivariate analysis shows that socio-economic factors including education of household head and respondent, water availability and access to media have strong positive association with hand washing with soap. Conclusion Gap between knowledge and practice still persists in hand washing practices. Long term and extensive initiatives can aware people about the effectiveness of hand washing.